Efficient CO2 catalytic hydrogenation over CuOx–ZnO/silicalite-1 with stable Cu+ species. Issue 19 (22nd August 2022) - Ma, Baorun; Pan, Hongxin; Yang, Fan; Liu, Xiaohui; Guo, Yong; Wang, Yanqin
Abstract : Efficient and stable CuO x –ZnO/S-1 catalysts for CO2 hydrogenation were inexpensively prepared, in which the ZnO–Cu2 O interface and silanol nests play key roles. Abstract : Cu-based/SiO2 nanocatalysts with Cu 0 or Cu + species as active sites have been widely investigated for CO2 hydrogenation. Here, 10CuO/silicalite-1(S-1) and 10CuO–2ZnO/S-1 catalysts were prepared inexpensively via a wet impregnation method. A 7.5% conversion of CO2 was reached and kept for 100 h over 10CuO–2ZnO/S-1 at 250 °C and 3 MPa. XPS and in situ CO-DRIFT showed that only Cu + species existed on the surfaces of both catalysts due to silanol nests from S-1. Moreover, there was synergism between Cu + species and ZnO on 10CuO–2ZnO/S-1, confirmed by H2 -TPR and in situ H–D exchange DRIFT, in which ZnO was responsible for H2 dissociation and the Cu + species of ZnO–Cu2 O interface adsorbed CO2 . Subsequently, the adsorbed CO2 was hydrogenated to CO via the carboxylate pathway by H species generated from ZnO. This study provides new insights into the Cu-based/SiO2, in which the ZnO–Cu2 O inter face and silanol nests from S-1 play key roles in CO2 hydrogenation, efficiently and steadily.